The Shi'a in modern South Asia: religion, history and politics - Jones, Justin; Qasmi, Ali Usman (Cambridge University Press, 2015)
"Explores various Shi'i communities across South Asia, revealing the many forms of Shi'i religion within this important region, and examining the responses of these communities to the many transformations of the modern world"